2009
DOI: 10.1111/j.1398-9995.2009.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐specific in vitro release of IL‐2, IL‐5, IL‐13 and IFN‐γ in patients with delayed‐type drug hypersensitivity

Abstract: The measurement of IL-2, IL-5, IL-13 or IFN-gamma or a combination thereof might be a useful in vitro tool for detection of T-cell sensitization to drugs. Secretion of these cytokines seems independent of the type of drug antigen and the phenotype of the drug reaction. A study including a higher number of patients and controls will be needed to determine the exact sensitivity and specificity of this test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 26 publications
1
78
3
1
Order By: Relevance
“…Therefore the sensitivity of both tests was lower than that previously found by the same group. 33,34 However, as previously reported by Lochmatter et al 35 and highlighted by Martin (Bonn, Germany), the combination of these tests with the assay of drug-specific cytokines (eg, IF-g, IL-2, IL-5, IL-8, and IL-12) can increase the sensitivity and specificity to 48% and 82%, respectively, in the study of Pichler's group presented at the DHM4.…”
Section: Nonimmediate (T Cell-mediated) Reactionsmentioning
confidence: 80%
“…Therefore the sensitivity of both tests was lower than that previously found by the same group. 33,34 However, as previously reported by Lochmatter et al 35 and highlighted by Martin (Bonn, Germany), the combination of these tests with the assay of drug-specific cytokines (eg, IF-g, IL-2, IL-5, IL-8, and IL-12) can increase the sensitivity and specificity to 48% and 82%, respectively, in the study of Pichler's group presented at the DHM4.…”
Section: Nonimmediate (T Cell-mediated) Reactionsmentioning
confidence: 80%
“…16 Previous studies have observed increases in IL-5 levels after an allergic reaction, but without pinpointing the cause of this increase. 8,[17][18][19] In the present study, the use of the Polyflux membrane significantly decreased peripheral eosinophil count and serum IL-5 levels. In addition, these indicators increased again in the few patients who resumed the use of the polysulfone membrane, suggesting that the Polyflux membrane improved HAE in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 76%
“…In vitro detection of drug-specific cytokine production by PBMCs appears to be an adequate alternative for the detection of drug hypersensitivities [6,9,[17][18][19]. In many reports, the total Tcell population in the cultures, including the non-proliferating T cells, was analyzed.…”
Section: Discussionmentioning
confidence: 99%